Workability and microstructural properties of red-mud-based geopolymer with different particle sizes. Issue 5 (8th May 2021) - Zhang, Jian; Li, Shucai; Li, Zhaofeng; Gao, Yifan; Liu, Chao; Qi, Yanhai
Abstract : Red mud (RM) can be used in large quantities in geopolymer technology to reduce the usage of ordinary Portland cement products. The effect of varying the particle size of RM on the potential reactivity of geopolymers and the properties of RM-based geopolymers was investigated in this study. Five different mean particle sizes (MPSs) were blended with blast-furnace slag to prepare RM-based geopolymers. The dissolution efficiency of the RM and the workability, hardening process, compressive strength and microstructure of RM-based geopolymers were analysed. The results showed that the dissolution efficiency of Al 3+ and Si 4+ decreased with an increase in the MPS, the setting time and fluidity of the RM-based geopolymer increased with a finer MPS, the compressive strength first decreased and then increased with increasing MPS and the RM-based geopolymer paste exhibited the rheological characteristics of the Herschel–Bulkley model. RM participated in the reaction and had a micro-aggregate effect. The effect of RM MPS on the properties of RM-based geopolymer was analysed by X-ray diffraction, infrared spectroscopy, mercury intrusion porosimetry and scanning electron microscopy.